Characterization of silylated modified clay nanoparticles and its functionality in PMMA. (1st February 2017) - Bee, Soo-Ling; Abdullah, M.A.A.; Mamat, Mazidah; Bee, Soo-Tueen; Sin, Lee Tin; Hui, David; Rahmat, A.R.
Abstract: The objective of this work was to investigate the effect of single and dual functionalized montmorillonite on the morphology, mechanical and thermal characteristics of the resulting PMMA nanocomposites. In this work, pristine sodium montmorillonite (Cloisite Na + ) and commercially organomodified montmorillonite (Cloisite 20A) were modified with silane coupling agent via silylation reaction to increase the clay's compatibility with poly (methyl methacrylate) (PMMA). The resulting nanofillers were then characterized using fourier transform infrared (FTIR), X-ray diffraction (XRD), CHN elemental analysis, nitrogen adsorption-desorption analysis and thermogravimetric analysis (TGA). The PMMA nanocomposites with intercalated structure were successfully fabricated by melt compounding of PMMA with s-Cloisite 20A. It was found that only microcomposites were formed using s-Cloisite Na + as evidenced by the results obtained by XRD. The structure and morphology of the as-prepared polymer hybrids were further characterized by Scanning Electron Microscopy (SEM). The effect of the interfacial interaction between the polymer and nanofillers, their microstructure as well as the influence of clay loading on the thermal and mechanical properties of the resulting products was also studied by means of TGA and tensile tester and hardness tester. The result shows that the thermal stability and tensile strength of the nanocomposites prepared by twice-modified clay surpassed the neat PMMA and PMMA/s-Cloisite Na + microcomposites, which is attributed to the formation of more favourable polymer-filler interaction in the PMMA/s-Cloisite 20A nanocomposites.